2021
DOI: 10.1016/j.resuscitation.2020.10.039
|View full text |Cite
|
Sign up to set email alerts
|

The performance of the National Early Warning Score and National Early Warning Score 2 in hospitalised patients infected by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)

Abstract: Introduction Since the introduction of the UK’s National Early Warning Score (NEWS) and its modification, NEWS2, Coronavirus disease 2019 (COVID-19), has caused a worldwide pandemic. NEWS and NEWS2 have good predictive abilities in patients with other infections and sepsis, however there is little evidence of their performance in COVID-19. Methods Using receiver-operating characteristics analyses, we used the area under the receiver operating characteristic (AUROC) curv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
82
2
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(99 citation statements)
references
References 35 publications
7
82
2
8
Order By: Relevance
“…A recent paper by Kostakis et al 7 found good discrimination for NEWS or NEWS2 (c-statistics 0.842–0.894) concluding that their results ‘support the national and international recommendations for the use of NEWS or NEWS2 for the assessment of acute-illness severity in patients with COVID-19.’ In contrast to our approach, Kostakis et al 7 used the last or ultimate recorded NEWS2/NEWS within 24 hours of death or ICU admission. We note that when we consider death within 24 hours of admission, our reported c-statistics for index NEWS/NEWS2 are comparable with those of Kostakis et al .…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…A recent paper by Kostakis et al 7 found good discrimination for NEWS or NEWS2 (c-statistics 0.842–0.894) concluding that their results ‘support the national and international recommendations for the use of NEWS or NEWS2 for the assessment of acute-illness severity in patients with COVID-19.’ In contrast to our approach, Kostakis et al 7 used the last or ultimate recorded NEWS2/NEWS within 24 hours of death or ICU admission. We note that when we consider death within 24 hours of admission, our reported c-statistics for index NEWS/NEWS2 are comparable with those of Kostakis et al .…”
Section: Discussionmentioning
confidence: 80%
“…We note that when we consider death within 24 hours of admission, our reported c-statistics for index NEWS/NEWS2 are comparable with those of Kostakis et al . 7 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this issue, Kostakis et al validate the use of the NEWS score in COVID patients using a Receiver Operator Characteristic (or ROC) curve, with the number of false positives plotted on the x axis and the number of true positives on the y axis 10 . The higher the arc of the curve, the greater the area under the curve (AUROC) and the closer the test gets to a perfect result – represented by a value of 1.…”
mentioning
confidence: 99%